Transcriptome analysis of CsWOX1 mutant and overexpressing lines reveals downstream genes regulating cucumber leaf morphogenesis - Anran Zhang; Xiangbao Li; Helong Zhang; Yanxin Jiang; Qingqing Li; Junjun Shen; Zheng Li (Vegetable Research)
WUSCHEL-related homeobox 1 (WOX1), categorized into the WUS clade, has been determined as the essential gene for leaf expansion as well as promoting leaf outgrowth along the mediolateral axis. The phenotypic characteristics of transgenic cucumber plants with CsWOX1 overexpression (CsWOX1-OE) and mutants (designated as mango fruit, mf) have been reported. Specifically, CsWOX1-OE cucumber plants exhibit leaves with a distinctive 'butterfly-shaped' appearance, while mf mutants show a rapid reduction in the area of their leaf tips. In this study, RNA-Seq was employed to sequence the transcriptome of CsWOX1-OE to reveal its differentially expressed genes (DEGs). Combined with the transcriptome sequencing data of the mf mutant, GO classification, and KEGG pathway enrichment analyses were performed, revealing new links between the WOX1 protein and many core plant regulatory pathways. The further joint analysis identified 80 common DEGs between CsWOX1-OE and mf, with a significant proportion of these common DEGs being annotated to the circadian pathway and the auxin polarity transport pathway. Six genes (CsGI, CsFKF1, CsRVE6, CsRVE8, CsABCB, and CsPin1At) were selected for Y1H and Dual-LUC interaction validation experiments. These experiments demonstrated that CsWOX1 directly targets the promoters of CsRVE6, which regulates leaf expansion, and CsPin1At, which is involved in auxin polarity transport, thereby promoting their transcription. In conclusion, these findings provide a foundation for exploring the potential regulatory mechanisms associated with CsWOX1, expecting to contribute to the construction of a more comprehensive gene network for leaf morphogenesis.